The World of Nothing - Kayukov, Valery A. (Journal of History Culture and Art Research, 2017)
The article presents a comparative analysis of knowledge about the world of nothingness. J. Boehme pointed to the fact that the world of Nothing is everlasting emptiness, where and wherein the material world could emerge. But the thing is that the world of absolute emptiness did not vanish at the moment of beginning of the world, quite the reverse, it has somehow been permanently enlarging. What will happen next is still a question. Perhaps our world will begin to be moving back on a new spiral of development, perhaps a real transition to the world of nothing will have appeared in this subtle place. For the present it is clear that these two worlds have not touched each other in mutually beneficial communication so far, and everything from our world passes into the world of nothing, and in general, the world of nothing ontologically appears to be much more existential than the world of apparent reality. What can give us some kind of key point at least, be some kind of organon in interaction with these two worlds - with the world of Nothing in which there is no matter and which cannot be perceived by any senses, and with the world of matter in which all senses are unstable and changeable? In our opinion, the only beacon and the instrument of knowledge can be the mind. To understand this phenomenon, by benefiting from a comparative methodology, this study investigates opinions of a number of philosophers, J. Boehme, G.V.F. Hegel, M. Heidegger, and J.P. Sartre, on the existence of the world of nothing.